Teachers’ and Students’ Perspectives on Technology Integration in EFL Instruction: Strategies for Fostering Autonomy and Overcoming Challenges in Indonesian High Schools - Nila Kencana (STAI Hubbulwathan Duri, 2025)
Technology integration is transforming English as a Foreign Language (EFL) instruction in Indonesian high schools. This study explores the role of technology in fostering student autonomy in EFL education and examines strategies employed by teachers to integrate technology effectively. A phenomenological approach was used, with data collected through semi-structured interviews and focus group discussions involving 20 students and 5 teachers from diverse Indonesian high schools. Thematic analysis revealed that technology enhances student autonomy by providing access to extensive resources, fostering collaboration, and delivering instant feedback. Teachers play a critical role in creating learner-centered environments using platforms like Google Classroom and various digital tools. However, challenges such as limited access to technology and inadequate infrastructure impede seamless integration. The study underscores the need for targeted investments in infrastructure, equitable access to digital tools, and comprehensive teacher training to address these challenges. Recommendations include equipping educators with skills to leverage technology effectively, integrating collaborative platforms into the curriculum, and prioritizing underserved areas for infrastructure development. Policymakers are urged to bridge digital divides and foster partnerships with technology providers to create sustainable EFL solutions. The findings have significant implications for curriculum design, teacher training, and policy development, promoting equitable and impactful technology use in EFL classrooms. Future efforts should focus on workshops and training programs to empower teachers with practical strategies for enhancing learner autonomy and fostering collaboration through digital tools.